African Home-Grown Innovations Take Off - Broadman, Harry G. (International Finance Corporation, Washington, DC, 2018)
Over the last decade African advances in technology, especially in the home-grown mobile banking sector, have shown how innovation can contribute to economic development across the continent. By understanding how the application of changes in technologies take hold globally—from initial discovery to new commercial products, processes, or services—private firms in Africa can better deploy investment into successful innovations to propel the continent’s productivity and growth.